Pleiotropic Functions and Biological Potentials of Silver Nanoparticles Synthesized by an Endophytic Fungus - Chandankere, Radhika; Chelliah, Jayabaskaran; Subban, Kamalraj; Shanadrahalli, Vanitha C.; Parvez, Amreesh; Zabed, Hossain M.; Sharma, Yogesh C.; Qi, Xianghui (Frontiers in Bioengineering and Biotechnology, 2020)
In recent years, the biological synthesis of silver nanoparticles (AgNPs) from microorganisms has become an emerging trend for developing biocompatible nanomaterials that finds applications in nano and biomedical sectors. In the present study, we demonstrated a facile, green and eco-friendly method for AgNPs synthesis using the endophytic fungi (Colletotrichum incarnatum DM16.3) isolated from medicinal plant Datura metel and its in vitro antithrombin and cytotoxic activity. At first, biosynthesis of colloidal AgNPs was predicted by visual observation of color change and UV-visible spectra demonstrated specific surface plasmon resonance peak at 420 nm which confirmed the presence of nanoparticles. Microscopic analyses revealed the structure of highly aggregated, spherical and crystalline AgNPs in the diameter range of 5–25 nm. Transform infrared spectroscopy (FT-IR) spectral analysis confirmed the presence of probable biomolecules required for the reduction of silver ions. In vitro evaluation of thrombin activity demonstrates that AgNPs could exert strong inhibition against both thrombin activity (87%) and thrombin generation (84%), respectively. Further, in silico based mechanistic analysis yielded a better insight in understanding the probable amino acids responsible for AgNPs binding with thrombin protein. Similarly, in vitro cytotoxicity of synthesized AgNPs on human epithelial cells using MTT assay did not produce any substantial effects after 24 h exposure which indicates excellent biocompatibility nature, whereas notable toxicity was observed on human cancerous (HeLa) cells at 50 μg/mL (IC50 value). In addition, assessment of AgNPs at 10 μg/mL concentration via crystal violet method on biofilm forming Gram-positive (Vibrio cholerae) and Gram-negative bacteria (Bacillus cereus) revealed inhibition up to 85 and 46%, respectively. Overall, this study showed the possibility of microbially synthesized AgNPs as a potent inhibitor for managing acute thrombosis and highlighted their role for other biomedical applications.